Ulnar nerve tuberculoma: A case report and literature review. (October 2016) - Song, Mingzhi; Sun, Xiaohong; Sun, Ran; Liu, Tao; Li, Gang; Liu, Song; Lu, Ming; Qu, Wei
Highlights: Peripheral nerve tuberculoma is very rare. The intraoperative situation was illustrated with photos and hand-painted renderings. We attempted to analyze the reasons for this rare disease. We introduced the surgical process in detail. Our experience may be useful for other surgeons. Abstract: Ulnar nerve tuberculoma is a rare case of tuberculous involvement of the peripheral nerve, which has attracted the attention of physicians. Here, we report the case of a patient with ulnar nerve tuberculoma. A 25-year-old patient presented progressive numbness on his left hand and forearm, and typical symptoms were not evident. The patient had no history of trauma or contact with any individuals with active tuberculosis. Exploratory surgery was performed and a granuloma-like lesion was found on the left ulnar nerve of the patient. The lesion was completely removed. We prepared hand-painted renderings for this rare disease for the first time, to the best of our knowledge. Histopathological examination of the specimen confirmed the presence of tuberculoma. After 1 year of adequate antitubercular treatment, the patient recovered fully. Doctors need the most detailed radiographic information and histological results to confirm the diagnosis of this rare disease. At present, surgery is an effective way to resolve symptoms of ulnar nerve tuberculoma.